Social Distance Into Factual Information Distance about COVID-19 in Indonesia Whatsapp Groups - Muhammad Taufiq Syam; Zulkifli Makmur; Askar Nur (Jurnal Ilmu Komunikasi, 2020)
WhatsApp has become a forum for communication and information related to the COVID-19 pandemic, so there are messages that ignore the identification and validation of news facts. This creates an information gap on WhatsApp. This study aims to analyze the form of information gaps related to information on the COVID-19 pandemic in Indonesia shared by WhatsApp group users. This research uses quantitative research methods, with data collection techniques through documentation of text messages and pictures, as well as the results of a survey conducted on WhatsApp group users. The results of this research indicate that the information gap in reporting the COVID-19 pandemic occurs due to information gaps in the form of uncertainty, strong beliefs and opportunities to choose information and decisions to choose information values. The substance of this research contributes in the form of new policy recommendations in assessing information gaps in social media by validating the truth of the facts in each message received and shared to another users.